Chromosome 2q gain and epigenetic silencing of GATA3 in microglandular adenosis of the breast. (31st December 2020) - Radner, Martin; van Luttikhuizen, Jana Lisa; Bartels, Stephan; Bublitz, Janin; Grote, Isabel; Rieger, Luisa; Christgen, Henriette; Stark, Helge; Werlein, Christopher; Lafos, Marcel; Steinemann, Doris; Lehmann, Ulrich; et al.
Abstract: Microglandular adenosis (MGA) represents a rare neoplasm of the mammary gland, which in a subset of cases may be associated with triple‐negative breast cancer (BC). The biology of MGA is poorly understood. In this study, eight MGA cases ( n  = 4 with and n  = 4 without associated BC) were subjected to a comprehensive characterization using immunohistochemistry, genome‐wide DNA copy number (CN) profiling, fluorescence in situ hybridization (FISH), next‐generation sequencing (NGS), and DNA methylation profiling using 850 K arrays and bisulfite pyrosequencing. Median patient age was 61 years (range 57–76 years). MGA lesions were estrogen receptor (ER)‐negative, progesterone receptor‐negative, HER2‐negative, and S100‐positive. DNA CN alterations (CNAs) were complex or limited to few gains and losses. CN gain on chromosome 2q was the most common CNA and was validated by FISH in five of eight cases. NGS demonstrated an average of two mutations per case (range 0–5) affecting 10 different genes ( ARID1A, ATM, CTNNB1, FBXW7, FGFR2, MET, PIK3CA, PMS2, PTEN, and TP53 ). CNAs and mutations were similar in MGA and adjacent BC, indicating clonal relatedness. DNA methylation profiling identified aberrant hypermethylation of CpG sites within GATA3, a key transcription factor required for luminal differentiation. Immunohistochemistry showed regular GATA3 protein expression in the normal mammary epithelium and in ER‐positive BC. Conversely, GATA3 was reduced or lost in all MGA cases tested (8/8). In conclusion, MGA is characterized by common CN gain on chromosome 2q and loss of GATA3. Epigenetic inactivation of GATA3 may provide a new clue to the peculiar biology of this rare neoplasia.